Effects of biosolids application on soil chemical properties in peri-urban agricultural systems - Nguyễn, Mạnh Khải (VNU, 2014)
The application of biosolids as a fertilizer in agricultural cultivation are common practices in many countries. This study investigates the effects of such practices in field experiments on Fluvisol and Acrisol soils in peri-urban Hanoi City. We compared biosolidfertilized vegetable/rice-dominated systems (biosolids applied as chicken manure (Acrisol in Vinh Phuc Province) or composted pig manure mixed with rice straw (Fluvisol in Ha Tay Province). The biosolids were applied at six different rates representing from 0 to 450% of the normal annual dose used by local farmers. The application of biosolids had highly significant positive effects on organic carbon (TOC%) and total nitrogen (Ntot%), when the six different treatments of composted manure and chicken manure were compared. The soil reverse aqua regia-extractable (Rev Aq Reg) Zn increased linearly with biosolids application rate at both sites and the linear regression showed Zn (mg kg-1) = 112.5 + 13.25×10-3×composted manure (t ha-1) (r2=0.58) or Zn (mg kg-1) = 43.77 + 35.04×10-3×chicken manure (t ha-1) (r2=0.73), whereas Cu (Rev Aq Reg) only increased significantly at the Vinh Phuc site. The Cd and Pb (Rev Aq Reg) concentration is not clearly different from the control after short-term (one time) application of biosolids. The application of biosolids increased the EDTA-extractable fraction of Cd, Cu and Zn, but had no effect on NH4NO3-extractable fractions of these elements.